2020
DOI: 10.51200/mjbe.vi.2890
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Factors That Affecting Youth Unemployment in Malaysia

Abstract: The purpose for this research was to identify the impact of the macroeconomic factors that is inflation rate, Gross Domestic Product (GDP) and Foreign Direct Investment (FDI) towards to youth unemployment in Malaysia. This research collects the data from Bloomberg and the data that have been collected will be analyse using the Eviews software. The result of this research shows that inflation rate and GDP have a negative relationship with youth unemployment. Meanwhile for the FDI, it shows a positive relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The unemployment statistics in Malaysia show that young people constitute the highest unemployment rate at 10.9%, slightly lower than the unemployment ratio in Southeast Asia at 12.2%. These figures position Malaysia's unemployment rate as the third highest, after the Philippines and Indonesia (Michael & Geetha, 2020). In addition, Welsh and Cheng (2020) asserted that research has indicated high unemployment rates among youths under 25 years old, primarily attributed to their lack of skills.…”
Section: Problem Statementmentioning
confidence: 99%
“…The unemployment statistics in Malaysia show that young people constitute the highest unemployment rate at 10.9%, slightly lower than the unemployment ratio in Southeast Asia at 12.2%. These figures position Malaysia's unemployment rate as the third highest, after the Philippines and Indonesia (Michael & Geetha, 2020). In addition, Welsh and Cheng (2020) asserted that research has indicated high unemployment rates among youths under 25 years old, primarily attributed to their lack of skills.…”
Section: Problem Statementmentioning
confidence: 99%
“…Increase in unemployment, with the biggest effect likely to be in low-skill and decrease productivity sectors, such as tourism and retail some countries because it only measures the productivity of those who work (Gandy and Mulhearn, 2021). According to Michael and Geetha (2020), unemployment is a situation in which people who are actively looking for work are unable to find work. Dosi, Pereira, Roventini and Virgillito (2018) suggested when the Slovakia unemployment benefits are reduced significantly; macroeconomic conditions tend to deteriorate in terms of long-run growth of earnings and productivity.…”
Section: Unemploymentmentioning
confidence: 99%
“…The significant numbers of young people in NEET reflect a relatively high portion of young people around the world who are currently not contributing to either national development or self-development. Young people are more vulnerable than adults (Michael & Geetha, 2020). Globally, the ratio of young-to-adults to be unemployed is 3:1.…”
Section: Introductionmentioning
confidence: 99%